Fundamental approaches to software engineering : 21st International Conference, FASE 2018, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings /: 21st International Conference, FASE 2018, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings. (2018) - Unknown
No abstract available